Simulation training for medical emergencies of dental patients: A review of the dental literature - Naotaka Kishimoto; Takuro Sanuki; Younan Liu; Simon D. Tran; Kenji Seo (Elsevier, 2023)
In recent years, due to the aging of the population, the number of dental patients with comorbidities such as hypertension and diabetes has increased. Although it has been reported that these patients are increasingly developing medical emergencies during their dental treatments, many dental providers still do not possess the skills to manage medical emergencies appropriately. Simulation training is essential to improve this situation however, there is no report describing how to conduct an effective simulation in detail for dental office medical emergencies. The purpose of this review is to provide information on simulations that is effective and practical. The authors will highlight the key characteristics for providing effective simulation trainings, such as the selection of simulators, simulation locations, instructors, debriefings, methods for evaluating educational effectiveness, and the use of telesimulation as a method for simulation training due to the global COVID-19 pandemic. In addition, this review provides recommendations on tailoring an ideal simulation training course for those who wish to create one. The authors hope that this review will promote the spread of effective simulation training and in turn, contribute to improving the medical safety of dental patients.